Teaching Reading in Contemporary Pedagogic Discourse - Raquel Goulart Barreto; Glaucia Campos Guimarães (Universidade Federal do Rio Grande do Sul, 2015)
Based on the analysis of an action research on reading, this paper aims at discussing reading and text production at schools nowadays. It is divided into four sections, as follows: (1) pedagogic discourse as the arena for struggling for hegemony, involving the ways information and communication technologies are to be recontextualized in school practices; (2) means to approach meaning production in teaching reading; (3) results of the action research developed in a public school, so as to provide the basis for other recontextualization movements; and (4) dimensions of teachers' work, especially as far as reading and text production are concerned.